Modernization of the Faradje' Ritual as A Form of Adaptation of the Tradition of the Surya Negara Palace in the Era of Modernization and Globalization - Desfianta, Arya; Ramadhan, Iwan; Wahyuni, Fauziyah Sri; Wiyono, Hadi; Imanulyaqin, Muhammad Nur (Universitas Tanjungpura, 2025)
This study aims to explore information about the Faradje’ ritual, a unique tradition of the Malay ethnic Sanggau community, and to understand how this ritual endures in the era of modernization and globalization. The Sanggau community performs the Faradje’ ritual annually as a form of warding off misfortune and an effort to maintain regional tranquility. The methods used in this research include interviews, observation, and documentation. The results show that although there are changes in the implementation of the ritual, such as the use of materials and tools, the essence of the Faradje’ ritual remains preserved. This ritual functions as a means to strengthen social bonds and local cultural identity amid the challenges of globalization. This study is expected to contribute to the understanding of cultural transformation and the preservation of traditions in the modern era.